Physiological, perceptual and performance responses associated with self-selected versus standardized recovery periods during a repeated sprint protocol in elite youth football players: A preliminary study - Gibson, N.; Brownstein, C.; Ball, D.; Twist, C. (Pediatric Exercise Science, 2017)
Purpose: To examine the physiological and perceptual responses of youth footballers to a repeated sprint protocol employing standardized and self-selected recovery. Methods: Eleven male participants (13.7 ± 1.1 years) performed a repeated sprint assessment comprising 10 × 30 m efforts. Employing a randomized cross-over design, repeated sprints were performed using 30 s and self-selected recovery periods. Heart rate was monitored continuously with ratings of perceived exertion (RPE) and lower body muscle power measured 2 min after the final sprint. The concentration of blood lactate was measured at 2, 5 and 7 min post sprinting. Magnitude of effects were reported using effect size (ES) statistics ± 90% confidence interval and percentage differences. Differences between trials were examined using paired student t tests (p < .05). Results: Self-selected recovery resulted in most likely shorter recovery times (57.7%; ES 1.55 ± 0.5; p < .01), a most likely increase in percentage decrement (65%; ES 0.36 ± 0.21; p = .12), very likely lower heart rate recovery (-58.9%; ES -1.10 ± 0.72; p = .05), and likely higher blood lactate concentration (p = .08-0.02). Differences in lower body power and RPE were unclear (p > .05). Conclusion: Self-selected recovery periods compromise repeated sprint performance.